CTRP9 Mitigates the Progression of Arteriovenous Shunt-Induced Pulmonary Artery Hypertension in Rats - Hua Guan; Xiaofeng Yang; Tao Shi; Yongjian Zhang; Aoqi Xiang; Yongxin Li (Cardiovascular Therapeutics)
The present study is aimed at investigating the molecular mechanism of C1q/TNF-related protein 9 (CTRP9) and providing a new perspective in arteriovenous shunt-induced pulmonary arterial hypertension (PAH). PAH was established by an arteriovenous shunt placement performed in rats. Adenovirus(Ad)-CTRP9 and Ad-green fluorescent protein viral particles were injected into the rats through the tail vein. Following 12 weeks, the mean pulmonary arterial pressure (mPAP) and right ventricular systolic pressure (RVSP) were measured and morphological analysis was conducted to confirm the establishment of the PAH model. The systemic elevation of CTRP9 maintained pulmonary vascular homeostasis and protected the rats from dysfunctional and abnormal remodeling. CTRP9 attenuated the pulmonary vascular remodeling in the shunt group by decreasing the mPAP and RVSP, which was associated with suppressed inflammation, apoptosis, and extracellular matrix injury. In addition, CTRP9 dramatically increased the phosphorylation of AKT and p38-MAPK in the lung tissues of shunt-operated animals. These findings suggest a previously unrecognized effect of CTRP9 in pulmonary vascular homeostasis during PAH pathogenesis.